2023
DOI: 10.1021/acs.organomet.3c00132
|View full text |Cite
|
Sign up to set email alerts
|

NNN Pincer-Manganese-Catalyzed Guerbet-Type β-Alkylation of Alcohols under Microwave Irradiation

Abstract: A series of manganese carbonyl complexes based on bis(imino)pyridine ligands of the type R2 NNN (R = Cy, i Pr, Ph, p-FC 6 H 4 ) were synthesized. While the complex appears to be an NN bidentate-Mn(I) triscarbonyl species in the solid state, in solution, there is a gradual loss of carbon monoxide leading first to an NNN pincer-Mn(I) biscarbonyl complex, which finally disproportionates to an NNN pincer-Mn(II) dibromide and an NNN pincer-Mn(0) complex. Evidence for this transformation has been obtained from singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 100 publications
0
3
0
Order By: Relevance
“…The NNN pincer–Ru phosphine complexes 7 and 8 containing the p -F and p -CF 3 groups were synthesized in good yields by treatment of the corresponding ligands , , with RuCl 2 (PPh 3 ) 3 under an argon atmosphere at reflux for 12 h, and the NNN pincer–Ru phosphine complex 9 with a p -OMe moiety was synthesized in a similar fashion but at room temperature, followed by washing with diethyl ether and hexane (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
“…The NNN pincer–Ru phosphine complexes 7 and 8 containing the p -F and p -CF 3 groups were synthesized in good yields by treatment of the corresponding ligands , , with RuCl 2 (PPh 3 ) 3 under an argon atmosphere at reflux for 12 h, and the NNN pincer–Ru phosphine complex 9 with a p -OMe moiety was synthesized in a similar fashion but at room temperature, followed by washing with diethyl ether and hexane (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
“…However, it was observed that microwave heating produced better results than conventional heating, with unprecedented TONs. 61 2.2.6. Co-based catalysts.…”
Section: B-alkylation Of Secondary Alcohols With Primary Alcoholsmentioning
confidence: 99%
“…66 Scheme 16 Mn-catalysed b-alkylation of secondary alcohols with primary alcohols (ref. [59][60][61].…”
Section: B-alkylation Of Secondary Alcohols With Primary Alcoholsmentioning
confidence: 99%